2023
DOI: 10.1002/zoo.21774
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting captive female giraffe stress response: Male presence, small enclosure, and low temperature

Abstract: To improve animal welfare based on suitable social housing conditions, it is important to understand the factors that trigger high‐stress responses. Wild giraffes live in a fission–fusion society and males and females are rarely in the same herd for a long period. The captive condition of belonging to a herd with the same individuals for months or years is uncommon in nature. To understand the effect of male presence on female stress levels, fecal glucocorticoid metabolite (fGCM) levels and social interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Warmth: Research identified that giraffe become physiologically and behaviourally stressed when they experience colder external temperatures [41]; therefore, a sound foundation to good giraffe health is to ensure they do not lose excess heat in cold weather. Giraffes evolved for evaporation of heat away from the body and have physiological mechanisms specific for life in a hot environment [42].…”
Section: Giraffe W-e-l-f-a-r-ementioning
confidence: 99%
See 1 more Smart Citation
“…Warmth: Research identified that giraffe become physiologically and behaviourally stressed when they experience colder external temperatures [41]; therefore, a sound foundation to good giraffe health is to ensure they do not lose excess heat in cold weather. Giraffes evolved for evaporation of heat away from the body and have physiological mechanisms specific for life in a hot environment [42].…”
Section: Giraffe W-e-l-f-a-r-ementioning
confidence: 99%
“…A social group that provides multiple opportunities to be with preferred associates as well as spending time alone is an important way to promote good welfare [45]. For example, incidences of dominance and aggression increase during forced social encounters in small herds [41], as giraffe have limited choice of associate and, therefore, cannot benefit from social enrichment. Devices to prolong foraging [46] are useful in reducing oral stereotypies.…”
Section: Giraffe W-e-l-f-a-r-ementioning
confidence: 99%